ROLE OF ANTI-THROMBOTIC THERAPY FOR RECURRENT PREGNANCY LOSS DUE TO ANTI-PHOSPHOLIPID SYNDROME - Fawad, Saadia (Journal of Ayub Medical College Abbottabad, 2010)
Background: Recurrent pregnancy loss is a major health problem effecting 1-2% of women of reproductive age. Its causes range from chromosomal abnormalities to endocrinological factors and thrombophilia related factors. Treating thrombophilias especially antiphospholipid syndrome with low dose aspirin and low molecular weight heparin improves foetal outcome. This study will add local data to already existing knowledge. Method: Sixty selected patients from gynaecology OPD of Aero Hospital with clinical and/or serological findings of antiphospholipid syndrome from February 2009 to January 2011 were given aspirin 75 mg once daily and enoxaparine 40 mg subcutaneously once daily from 6-8 weeks to 35 and 37 weeks respectively. Results: Ninety-three percent of patients achieved live birth. Out of these 75% patients delivered at term and 18% had preterm delivered. Four (7%) had early pregnancy loss and only one had early neonatal death due to extreme prematurity. None of patients experienced any major hemorrhagic complications. Conclusion: Use of low dose aspirin and low molecular weight heparin is safe in pregnancy and improve foetal outcome in patients with recurrent pregnancy loss due to antiphospholipids syndrome. Keywords: Recurrent pregnancy loss, Antiphospholipid syndrome, low molecular weight heparin